ANALYSIS OF FACTORS AFFECTING CONSUMER SATISFACTION IN USING THE OVO DIGITAL WALLET - SY, Supriyatin (Sean Institute, 2021)
The purpose of this research is to establish how the service quality and user-friendliness of the OVO digital wallet contribute to overall customer satisfaction (studies on OVO users in Jatinegara district, East Jakarta). The research that was conducted was of the descriptive quantitative variety, and one of the methods for gathering data was the use of questionnaires. The results of the analysis of the data obtained in this study indicated that the quality of the service provided has an effect on the level of customer satisfaction. Specifically, the P-Value of 0.006 indicated that the probability value was less than 0.05, which indicates that this hypothesis is supported by the data. There is a correlation between ease of use and customer happiness, as indicated by the P-Value of 0.000, which indicates that the likelihood value is lower than 0.05. Both the Level of Service Quality and the Ease of Use are Important Factors That Influence Customers' Level of Satisfaction.